The Self‐Healing Potential of Triazole‐Pyridine‐Based Metallopolymers. Issue 7 (22nd December 2014) - Sandmann, Benedict; Happ, Bobby; Kupfer, Stephan; Schacher, Felix H.; Hager, Martin D.; Schubert, Ulrich S.; Schubert, S.; Manners, I.; Newkome, G. R.; Schubert, U. S.
<x xml:space="preserve">Abstract</x> The development of artificial self‐healing materials represents an emerging and challenging field in material science. Inspired by nature—for instance by the self‐healing of mussel byssus threads—metallopolymers gain more and more attention as attractive self‐healing materials. These compounds are able to combine the properties of both polymers and metal–ligand interactions. A novel metallopolymer is developed consisting of attached bidentate triazole‐pyridine (TRZ‐py) ligands and a low glass transition temperature (Tg) lauryl methacrylate backbone. The polymer is cross‐linked with different Fe(II) and Co(II) salts. The resulting materials exhibit promising self‐healing performance within time intervals of 5.5 to 26.5 h at moderate temperatures of 50 to 100 °C. The materials are characterized by X‐ray scattering (SAXS), UV–Vis spectroscopy, and light microscopy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>